Green Economics in Global Perspective based on Bibliometric Review - Loso Judijanto (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis of green economics literature from 1967 to 2024, highlighting thematic clusters, research trends, potential research topics, and author collaborations. The analysis identifies key themes such as green innovation, energy, economic activities, green investment, and policy frameworks, emphasizing the multifaceted nature of the field. Temporal trends reveal a progression from foundational economic activities to a focus on green innovation and integrated policy initiatives. Potential research areas include financial instruments like green bonds, regulatory frameworks, and the economic benefits of sustainable practices. The author collaboration network shows significant cooperative efforts, with tightly-knit clusters of researchers driving advancements in green economics. This interdisciplinary and collaborative nature suggests that future research will benefit from continued partnerships and integrated approaches to sustainability.